Effect of water management and polyolefin-coated urea on growth and nitrogen uptake of indica rice - Oluwarotimi, O.; Fashola, O.O.; Hayashi, K.; Wakatsuki, T. (Informa UK Limited, 2002)
Poor water management and high nitrogen (N) losses are the key problems faced by rice farmers under rainfed inland valley systems. There is a need to evaluate different N fertilizers so as to identify one that could withstand these problems. The performance of polyolefin-coated urea (POCU) was therefore compared with conventional urea in a pot experiment with indica rice (Oryza sativa L. cv. IR36), using two water management systems: 1) Submerged condition referred to as good water management (GWM), and 2) excessive irrigation (over 4000mm in 120 days) referred to as poor water management (PWM). The study was carried out during 1997 and 1998 cropping seasons under glasshouse conditions. For PWM in 1997, the pots were subjected to leaching only whereas in 1998, they were subjected to both surface runoff and leaching. For both cropping seasons, POCU-treated plants under PWM had a significantly higher grain yield (377.5 and 343.0 gm_2) than urea-treated plants (316.5 and 260.5 gm_2). In addition, POCU-treated plants had a significantly higher number of grains per panicle than ureatreated plants. In 1998, both the partial factor productivity of applied N and the agronomic nitrogen-use efficiency of POCUtreated plants under GWM and PWM were significantly higher than those of urea-treated plants. It can be inferred that (using sandy soils and under PWM), POCU could perform significantly better than conventional urea. This finding is important, considering the usually high nitrogen losses in rice-growing inland valley swamps.